200 embroidered flowers : hand embroidery stitches and projects for flowers, leaves and foliage - Gula, Kristen (Sewandso, 2018)
Learn how to stitch all your favourite flowers, leaves and foliage, with this is collection of tutorials for 200 embroidered flowers and foliage. Discover how to stitch beautiful blooms including roses, daisies, daffodils, pansies and buttercups as well as more exotic blooms.